Predictors of Morbidity and Mortality in Organophosphorus Poisoning: A Case Study in Rural Hospital in Karnataka, India - Banday, Tanveer Hassan (N Am J Med Sci, 2015)
BACKGROUND: Organophosphorus (OP) pesticides poisoning can result from occupational, accidental or intentional exposure. Clinical manifestations include cholinergic syndromes, central nervous (CNS) system and cardiovascular disorders. Death is usually due to cardiovascular and respiratory failure. AIM: To evaluate various parameters that can predict outcome of patients in OP poisoning. MATERIALS AND METHODS: A prospective study conducted in Department of Medicine, Adichunchingiri Institute Of medical Sciences and Research Centre, Karnataka, over period of 1 year. Diagnosis of OP poisoning was based on clinical history of exposure to OP compound and low serum pseudocholinesterase levels. RESULTS: In the present study 133 patients were enrolled, out of which 98.5% were suicidal cases and only 1.5% had accidental exposure. Majority of cases were young male, with F/M ratio 1:3.2. Mortality rates were higher in younger people and in patients who required prolonged ventilator support. The mortality rate was directly proportional to amount of poison consumed, lag time, organ failure (Acute Renal Failure) and plasma pseudocholinesterase levels. Acute complications were frequently noted and were related to morbidity and mortality. No strict relationship was found between liver dysfunction, electrolyte disturbance and clinical outcome. CONCLUSION: This case study concluded that mortality is directly proportionate to the lag time, amount of OP substances consumed, clinical severity, pseudocholinesterase levels, Acute renal failure and duration of ventilatory support. This study highlights the importance of rapid diagnosis, and initiation of early and effective treatment, which may result in less number complications and also decreases the mortality rates.